2007
DOI: 10.1007/s00408-007-9000-7
|View full text |Cite|
|
Sign up to set email alerts
|

Elevated Levels of IL-18 in Plasma and Skeletal Muscle in Chronic Obstructive Pulmonary Disease

Abstract: The aim of this study was to test the hypothesis that systemic inflammation in patients with chronic obstructive pulmonary disease (COPD) is accompanied by enhanced interleukin 18 (IL-18) expression in skeletal muscle, which may precede muscle weight loss. Twenty patients with moderate to severe COPD [12 women, 66 +/- 9.4 years of age and forced expiratory volume in 1 second (FEV(1)) of 32% +/- 12 % of predicted value] and 20 healthy age-, gender-, and body mass index (BMI)-matched controls (10 nonsymptomatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 51 publications
7
48
2
Order By: Relevance
“…Although the presence of a degree of increased inflammatory markers in circulation is demonstrated [7], it is still unclear whether a similar local inflammatory process is present in peripheral skeletal muscles and might thus contribute to muscle fibre-type shift, decreased angiogenesis and eventual muscle wasting and cachexia. The relevance of this question is reflected in a series of recent studies which specifically addressed this point [13,14,15,16]. Furthermore, systemic effects of COPD were correlated with altered plasma levels of hormones [such as cortisol, leptin, ghrelin and insulin-like growth factor-1 (IGF-1)] during increased inflammation and catabolism [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Although the presence of a degree of increased inflammatory markers in circulation is demonstrated [7], it is still unclear whether a similar local inflammatory process is present in peripheral skeletal muscles and might thus contribute to muscle fibre-type shift, decreased angiogenesis and eventual muscle wasting and cachexia. The relevance of this question is reflected in a series of recent studies which specifically addressed this point [13,14,15,16]. Furthermore, systemic effects of COPD were correlated with altered plasma levels of hormones [such as cortisol, leptin, ghrelin and insulin-like growth factor-1 (IGF-1)] during increased inflammation and catabolism [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…01. the expression of IFN-γ [7] . Another study showed [8,9] that IL-18 can inhibit a variety of tumors, the production of malignant ascites, and can prevent tumors from metastasizing to the lung or from infi ltrating into surrounding tissues, and, as a result, can extend the survival time. Furthermore, the anti-tumor activity of IL-18 is not dependent on internal factors of IL-12 and IFN-γ [10] .…”
Section: Discussionmentioning
confidence: 98%
“…Its relationship to loss of muscle mass or strength, however, is not clearly defined. Although inflammation-related proteins in plasma, e.g., TNF-␣ (76 -78), IL-6 (76 -80), C-reactive protein (CRP) (76,78,80,81), and muscle, e.g., TNF-␣ (82), have often been demonstrated to be higher in patients with COPD compared with healthy controls, other reports indicated the contrary (22,72) or showed no difference between these groups (9,72,83). Similarly, nuclear transcription factor-␤ (NF-B) DNA-binding activity and inducible nitric oxide synthase have been found in one study to be higher in COPD patients with lower body mass index than those with higher body mass index (84), whereas another study reported no difference in inducible nitric oxide synthase levels in relationship to body mass in these patients (82).…”
Section: Relationship Between Inflammation and Muscle Dysfunction In mentioning
confidence: 96%
“…The inflammatory response can be detected early as reflected by an increased number of circulating leukocytes and cytokines in the plasma during some exercise stimuli (7). If the exercise stimulus is not excessive, a cellular and mediator response consistent with an anti-inflammatory and immunoregulatory benefit is induced (8,9). In the event of injurious exercise, which often has either an eccentric (lengthening) or an unaccustomed component, a proinflammatory response seems to dominate initially, followed by a later phase of regeneration and repair (7,10).…”
mentioning
confidence: 97%